2015
DOI: 10.1016/j.immuni.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

The MicroRNA-132 and MicroRNA-212 Cluster Regulates Hematopoietic Stem Cell Maintenance and Survival with Age by Buffering FOXO3 Expression

Abstract: Summary MicroRNAs are critical post-transcriptional regulators of hematopoietic cell-fate decisions, though little remains known about their role in aging hematopoietic stem cells (HSCs). We found that the microRNA-212/132 cluster (Mirc19) is enriched in HSCs and is up-regulated during aging. Both over-expression and deletion of microRNAs in this cluster leads to inappropriate hematopoiesis with age. Enforced expression of miR-132 in the bone marrow of mice led to rapid HSC cycling and depletion. A genetic del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 39 publications
2
77
1
Order By: Relevance
“…We have recently shown that this microRNA cluster helps maintain normal hematopoietic stem cell output with age by buffering Foxo3 protein levels (Mehta et al, 2015). The current study demonstrates that miR-212/132 maintains B cell output through a different mechanism, serving more as a gatekeeper that modulates Sox4 protein levels when increased B cell output is required.…”
Section: Microrna-132 Protects E-myc Mice From B Cell Leukemia Develmentioning
confidence: 67%
See 2 more Smart Citations
“…We have recently shown that this microRNA cluster helps maintain normal hematopoietic stem cell output with age by buffering Foxo3 protein levels (Mehta et al, 2015). The current study demonstrates that miR-212/132 maintains B cell output through a different mechanism, serving more as a gatekeeper that modulates Sox4 protein levels when increased B cell output is required.…”
Section: Microrna-132 Protects E-myc Mice From B Cell Leukemia Develmentioning
confidence: 67%
“…We have previously shown that Sox4 mRNA expression levels are decreased in the bone marrow of WT miR-132 mice compared with WT MG controls (Mehta et al, 2015). Sox4 has a conserved, computationally predicted 7mer-m8 binding site for miR-132 (Fig.…”
Section: Enforced Expression Of Microrna-132 Inhibits B Cell Developmentmentioning
confidence: 89%
See 1 more Smart Citation
“…Studies of vascular component in the formation of HSCs niches allowed have a new vision of the endosteal niche as it became clear that the influence of this region is not confined to the endosteal surface, as has been assumed initially [145,146]. As has already been mentioned, the BM in the endosteal region is well vascularized with arterioles and venous sinusoids with CAR-cells [105].…”
Section: Perivascular and Endothelial Cellsmentioning
confidence: 90%
“…Thus enhancement of miR-132 expression in the BM of mice stimulates the proliferation of HSCs and decreases their number. It is notable that miR-132 effect is mediated by the transcription factor FOXO3 [146].…”
Section: Intracellular Factorsmentioning
confidence: 99%